Implementation of Information Technology and Job Flexibility on Driver Performance Through Job Satisfaction as an Intervening Variable for Gojek (Go-Ride) Partners in Bukittinggi City - Ai Elis Karlinda; Silvia Sari (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
This study aims to determine the effect of the implementation of information technology and job flexibility on driver performance through job satisfaction as an intervening variable for gojek (go-ride) partners in Bukittinggi City. This study uses secondary data. The sampling technique in this study was using the slovin formula. The number of samples obtained as many as 90 respondents. The analytical method of this research uses multiple linear regression analysis and path analysis. From this study it was concluded that the implementation of information technology had a significant positive effect on job satisfaction, job flexibility had a significant positive effect on job satisfaction, information technology had a significant positive effect on driver performance, job flexibility had a significant positive effect on driver performance, job satisfaction had a positive and significant effect on driver performance. driver performance, information technology implementation has a significant positive effect on driver performance intervened by job satisfaction, job flexibility has a significant positive effect on driver performance intervened by job satisfaction.